Pengaruh Strategi Self Management Dalam Konseling Kelompok Terhadap Kedisiplinan Belajar Siswa Kelas XI IPS 2 SMA Giki 1 Surabaya - Ardiansyah, Muh. Irzal; Sutijono, Sutijono (RISDA : Jurnal Pemikiran dan Pendidikan Islam, 2021)
Education can not be separated from the emergence of various problems, one of which is the lack of discipline in student learning in the learning process. The purpose of this study was to determine the effect of group counseling services with self-management strategies on the discipline of learning of class XI IPS 2 SMA GIKI 1 Surabaya. The data collection instruments used in this research were observation and measurement scale. The sampling technique used was purposive sampling. The sample obtained amounted to 5 students with low criteria. The research data analysis technique used the normality test and the t test. The results of data analysis show that the results of learning discipline that have been treated with self-management strategies are better than before getting treated. The result of the hypothesis test is a pretest of 93.80 and a posttest value of 122.0, namely 122.0> 93.80, while the results of the t test show 0.00 <0.05. So it can be concluded that there is a significant increase in the results of learning discipline using group counseling with self-management strategies in class XI IPS 2 SMA GIKI 1 Surabaya.